ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PELANGGAN DALAM MEMBAYAR REKENING LISTRIK (Studi Kasus pada Pelanggan yang Menunggak di PT. PLN (Persero) APJ Surakarta) - Ispraptono, F. Joko (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2009)
This research analyzes factors which influence the decision to pay electricity bills. Object of this research is the customers who are in arrears at APJ (Area Pelayanan dan Jaringan – Service and Network Area)Surakarta office. PT. PLN (Perusahaan Listrik Negara – State-owned Electricity Company). The problem of this research refers to high delinquent payment and receivable account in the company’s Key Performance Indicators (KPI), which are still high. Because of that, the problem of this research is formulated as follows : the influences of customers’ behavior to the customers’ decision to pay the delinquent electricity bills ?In analyzing the influences of customers’ resources, customers’ knowledge, customers’ attitude, the influence of customers’ personalities, and also customers’ social class and status to the decision to pay, this research uses questionnaires to collect data from 150 respondents, who are as samples from the customers, who are in arrears in the working areas of PT. PLN APJ Surakarta office, covering the Surakarta City, Sragen Regency, Wonogiri Regency, Karanganyar Regency, and Sukoharjo Regency. The data collected are then processed by using SPSS program version 14.The result of this research shows that customers’ resources gives positive influence to the decision to pay, the customers’ knowledge alse give positive influence to the decision to pay, the customers’ attitude influences positively to the decision to pay, the customers’ personalities has positive influence to the decision to pay , social class and social status also give positive influence to the decision to pay the electricity bills.